1974
DOI: 10.1037/h0036018
|View full text |Cite
|
Sign up to set email alerts
|

Beauty is talent: Task evaluation as a function of the performer's physical attractiveness.

Abstract: Male college subjects read an essay that supposedly had been written by a college freshman co-ed. They then evaluated the quality of the essay and the ability of its writer on several dimensions. By means of a photo attached to the essay, one third of the subjects were led to believe that the writer was physically attractive and one third that she was unattractive. The remaining subjects read the essay without any information about the writer's appearance. In addition, one half of the subjects read a version o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
202
2
13

Year Published

1985
1985
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(226 citation statements)
references
References 12 publications
9
202
2
13
Order By: Relevance
“…This lack of attention to the critical feature occurs in part because that feature is not directly relevant to the subject's task. (For example, the sex of the unfamiliar name was the controlling but irrele- vant feature in the sex-discrimination variation of Jacoby et al 's [1989] "becoming famous overnight" result; and the physical attractiveness of the author was the controlling but irrelevant cue in Landy & Sigall's [1974] halo effect result.) Second, the dependent measures for these effects typically are themselves evaluative judgments.…”
Section: Resultsmentioning
confidence: 99%
“…This lack of attention to the critical feature occurs in part because that feature is not directly relevant to the subject's task. (For example, the sex of the unfamiliar name was the controlling but irrele- vant feature in the sex-discrimination variation of Jacoby et al 's [1989] "becoming famous overnight" result; and the physical attractiveness of the author was the controlling but irrelevant cue in Landy & Sigall's [1974] halo effect result.) Second, the dependent measures for these effects typically are themselves evaluative judgments.…”
Section: Resultsmentioning
confidence: 99%
“…This "beauty premium" is confirmed by numerous findings demonstrating that facial attractiveness positively influences judgments by both familiar and unfamiliar perceivers in multiple domains and across cultures (Langlois et al 2000;Miller 1970). More attractive children and adults are considered to be healthier and fitter, to have greater social appeal, to have higher academic competence, and to be more confident and better adjusted than their less attractive counterparts (Landy and Sigall 1974;Langlois et al 2000;Mobius and Rosenblat 2006). More attractive individuals also are more successful in their attempts at persuasion (Landry et al 2005) and receive sizable wage premiums compared to less attractive individuals (Hamermesh and Biddle 1994).…”
Section: The Beauty Premiummentioning
confidence: 99%
“…For example, Dion, Berscheid, and Walster (1972) reported that attractive males and females are judged to be kinder, more interesting, more sociable, happier, stronger, of better character, and more likely to hold prestigious jobs. Similarly, Landy and Sigall (1974) found that essays attributed to a female student were judged by male students to be of higher quality when the stimulus materials included a photo that showed the author to be physically attractive, rather than unattractive. Downs and Lyons (1991) reported that defendant attractiveness was associated with judges levying smaller fines and lower bail levels in actual misdemeanor cases (although this relationship was weaker or absent in felony cases).…”
Section: Implicit Attitudes: Empirical Findingsmentioning
confidence: 99%